2021
DOI: 10.1186/s13049-021-00915-0
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital characteristics of COVID-19 patients in Helsinki – experience of the first wave of the pandemic

Abstract: Background There is a lack of knowledge how patients with COVID-19 disease differ from patients with similar signs or symptoms (but who will have a diagnosis other than COVID-19) in the prehospital setting. The aim of this study was to compare the characteristics of these two patient groups met by the emergency medical services. Methods All prehospital patients after the World Health Organisation (WHO) pandemic declaration 11.3.2020 until 30.6.2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Yet, testing was likely affected by practical problems such as poor domestic language skills or by lower test-seeking behaviour, or healthcare workers might have been more prone to direct persons speaking domestic languages to testing. Foreign language speakers were overrepresented in a previous study on prehospital COVID-19 patients in Helsinki, which may indicate delayed seeking of health care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, testing was likely affected by practical problems such as poor domestic language skills or by lower test-seeking behaviour, or healthcare workers might have been more prone to direct persons speaking domestic languages to testing. Foreign language speakers were overrepresented in a previous study on prehospital COVID-19 patients in Helsinki, which may indicate delayed seeking of health care [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used difficulty securing hospital acceptance as the dependent variable and duration of the states of emergency as the independent variable, adjusting for body temperature (>37.4°C), oxygen saturation without oxygen therapy at the trauma scene (<95%), age (>64 years), and systolic blood pressure (<90 mmHg), which might have influenced the difficulty securing hospital acceptance during the pandemic. 9,10 The time spent on the trauma scene during the states of emergency was stratified by trauma severity (less severe, moderately severe, severe, and life-threatening) and compared with that in the prepandemic period in 2019, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression was performed using the incidence of difficulty securing hospital acceptance as the dependent variable. We used difficulty securing hospital acceptance as the dependent variable and duration of the states of emergency as the independent variable, adjusting for body temperature (>37.4°C), oxygen saturation without oxygen therapy at the trauma scene (<95%), age (>64 years), and systolic blood pressure (<90 mmHg), which might have influenced the difficulty securing hospital acceptance during the pandemic 9,10 …”
Section: Methodsmentioning
confidence: 99%
“…Our study results showed that the addition of clinical signs such as body temperature ≥37.5 °C, respiratory rate ≥20 breaths/minute, and SpO 2 < 90% can improve the sensitivity of the screening protocol. Although these signs are also nonspecific, [ 11 , 13 , 14 ] positive COVID-19 cases are likely to present with tachycardia, tachypnea, and/or low SpO 2 . [ 9 ] By adding 2 or more of these additional variables, the sensitivity of the screening protocol increased, while the specificity and PPV decreased.…”
Section: Discussionmentioning
confidence: 99%